Improving the Biodiesel Production in Saccharomyces Cerevisiae: Metabolic Engineering and Enzyme Engineering - Kembaren, Riahna br (Indonesian Journal of Life Sciences, 2023)
The yeast Saccharomyces cerevisiae can produce fuels such as biodiesel using the biomass of lignocellulose. S. cerevisiae metabolize monosaccharide of lignocellulosic hydrolysates to supply fuels/energy globally without competition issue with food supply. Ethanol and free fatty acids (FFAs) are the precursors of biodiesel. S. cerevisiae is able to produce these precursors. S. cerevisiae synthesizes biodiesel from ethanol and fatty acyl-coenzyme A thioesters using wax ester acyltransferase (WS). Here, we review some recent strategies applied to metabolic engineering and enzyme engineering of S. cerevisiae for improving the yield of biodiesel. On the metabolic engineering strategy can be done by directing the carbon flux towards the fatty acids biosynthesis pathway through engineering some genes in the central carbon metabolism. By combined overexpression genes of Acetyl-CoA synthetase (ACS), Acetyl-CoA carboxylase (ACC1), and Fatty Acid Synthase (FAS) will improve biodiesel synthesis. In enzyme engineering, we can remove the allosteric inhibition control of Snf1 to Acetyl-CoA carboxylase ((ACC1), an enzyme that convert Acetyl Co-A to malonyl Co-A) by mutation of two phosphorylation site of ACC1 via site-directed mutagenesis which mutates serine1157,659 to alanine1157,629. This result in enhanced carbon flux to fatty acid synthesis and contribute to a higher yield of biodiesel.